Correlation of the cycle threshold value of SARS-CoV-2 by RT-PCR with biomarker levels in the prognosis of patients hospitalized with COVID-19 - Shweta Singhal; Geetika Rana; Atul K. Singh; Shekhar Pal; Shweta Thaledi (Journal of Family Medicine and Primary Care)
Background and Objective: The COVID-19 disease caused by SARS-CoV-2 was declared as pandemic by WHO soon after its emergence in 2019. This virus was known to cause serious clinical symptoms and severe illness. By using RT-PCR, which reports the cycle threshold value, the disease is diagnosed, whereas for the severity of the disease, biomarker levels, like IL-6, CRP, D-dimer, serum ferritin and serum procalcitonin, can be measured. We, thus, aimed to explore any potential correlation of the cycle threshold value and biomarker level with the outcome of COVID-19-positive hospitalized patients. Method: Patients with the cycle threshold (Ct) value <35 were included in the study and their initial Ct values were noted. Different biochemical parameters, such as C-reactive protein (CRP), serum ferritin, D-dimer, Interleukin-6 and serum procalcitonin, were assessed for severity. They were classified according to Ct value into three groups: Group 1 >30.0, Group 2 20.0–30.0 and Group 3 <20.0. Results: The study included 370 hospitalized COVID-19 patients with a mean age (mean ± SD) of 51.08 (16.58%) years and 250 (67.5%) males and 120 (32.4%) females. Comparison of data with outcome shows that IL-6, CRP amongst the biomarker and Ct value (deduced by RT-PCR test) were significantly correlated with the mortality (P value < 0.05). The ROC curve was also plotted for these parameters, which shows that IL-6, CRP, PCT and Ct value were better prognostic marker. Poor prognosis was found in Group 2 (Ct value 20.0–30.0) patients compared to Group 1 and Group 3. There was significant correlation (P value < 0.05) between Ct value and outcome of the patient. Interpretation and Conclusion: This study depicts that low Ct value and elevated levels of IL-6 and CRP can be used as a screening tool to detect the mortality in COVID-19 patients as they are significantly correlated with the mortality.